Breast tuberculosis: a case series - Moukit, Mounir; Bougrini, Youssef; Rahmoune, Mohammed; Allilou, Ismail; Babahabib, Abdellah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Tuberculosis is one of the leading infectious and contagious diseases, caused by bacteria belonging to the Mycobacterium family. Breast involvement ranks last among the extrapulmonary manifestations of tuberculosis but remains an important clinical condition that may present clinical and radiological similarities with breast cancer, thus requiring a thorough diagnostic approach including histological and/or bacteriological confirmation. This is a retrospective study conducted at the department of Gynecology and Obstetrics of the Military Hospital Moulay Ismail - Meknes, over a period of 4 years. A total of 6 cases of breast tuberculosis were observed, resulting in an incidence rate of 6 cases per 7600 women-years. The mean age of patients was 39 years. Signs of tuberculosis impregnation were found in 33% of cases. The clinical forms encountered, in descending order of frequency, were: diffuse form (50% of cases), nodular form (33% of cases), and sclerotic form (16% of cases). The radiological findings were almost always suggestive of a suspicious lesion. Diagnosis was primarily based on the histopathological study of breast biopsy. All our patients received a standard regimen of anti-tubercular treatment including: 4 months of Rifampicin, Isoniazid, Pyrazinamide, and Ethambutol followed by 2 months of Rifampicin and Isoniazid with favorable outcomes. Only one patient experienced a recurrence due to under dosing of Rifampicin, which was managed with a total of 9 months of treatment. One patient underwent additional surgical drainage. Early and thorough diagnosis of breast tuberculosis is crucial as it helps avoid mutilating surgery in often young women.